PENGEMBANGAN KURIKULUM BERDIFERENSIASI MATA PELAJARAN MATEMATIKA SMA UNTUK SISWA CERDAS ISTIMEWA DAN BERBAKAT ISTIMEWA DI KELAS AKSELERASI - Murtianto, Yanuar Hery (Jurnal Pembelajaran Matematika, 2013)
Abstract: The research was aimed at: (1) formulating the needs of mathematics curriculum for gifted and talented students in acceleration class; (2) developing model prototype of differentiated mathematics curriculum of senior high school in acceleration class; (3) finding out the appropriateness of the differentiated mathematics curriculum that was developed.Research and development method was used to produce the model of mathematics curriculum. This method consisted of some steps, namely: (1) the preliminary step including field observation and literary research; (2) the development step including mathematics curriculum analysis and prototype design to be model differentiated mathematics curriculum; and (3) evaluation step to examine the final design of differentiated mathematics curriculum.Findings of the results were: 1) the need of the mathematics is concerned with: (a) the repetition of material minimum, (b) the effectiveness of the compacting of time (c) encourage gifted and talented students to think at a high level, (d) in accordance with the national curriculum tailored to the guidelines for the implementation of accelerated learning program (e) relative ready to use on the condition that a minimum school, 2) to develop a prototype model of differentiated curriculum in high school math class acceleration is done by: (a) analytical standards of competence and competence elementary school and high school mathematics, (b) identify standards and basic competencies based on the revised Bloom's taxonomy, (c) mapping standards and basic competencies essential, (d) the escalation of basic competence, (e) develop an indicator based on the escalation of basic competence, ( f) determine the allocation of time on each indicator, (g) organize competency standards, basic competency and escalated of indicators into structure of the semester (h) determine the allocation of time in each half, and 3) the results of the evaluation showed: (a) from in terms of the feasibility of the content of the prospective users of the respondent, the result that differentiated curriculum is good since was responded very good and good as big as 95%, (b) in terms of linguistic, with the result that differentiated curriculum is good since was responded good as big as 100%, (c) the presentation of the curriculum in terms the result that differentiated curriculum was developed is good since was responded very good and good as big as 95%, and (d) in terms of the potential users of the product from graphic, the result that differentiated curriculum is good since was responded very good and good as big as 100%. Besides the evaluation of the design is also made evaluation of differentiated mathematics curriculum content that includes seven components: (a) an accelerated rate of learning by repetition at least 75% of respondents gave very appropriate responses, 25% responded accordingly, (b) control the national curriculum (KTSP) in a shorter time 100% of respondents responded very appropriate, (c) material that is abstract, complex and deep 100% of respondents responded accordingly, (d) the use of skills learned in applying problem-solving strategies 75% of respondents said the suit, 25% of respondents said quite appropriate, (e) oriented learners 100% of respondents said that accordingly, (f) to apply research skills appropriate 75% of respondents said that, 25% said quite appropriate, and (g) motivate students to learn independent is responsed appropriate by the respondent of 100%.Key words: Differentiated Mathematics Curriculum, Gifted, Acceleration.